2020
DOI: 10.3390/molecules25245983
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Phenanthrenes from Juncus tenuis: Isolation and Diversity-Oriented Semisynthetic Modification

Abstract: The occurrence of phenanthrenes is limited in nature, with such compounds identified only in some plant families. Phenanthrenes were described to have a wide range of pharmacological activities, and numerous research programs have targeted semisynthetic derivatives of the phenanthrene skeleton. The aims of this study were the phytochemical investigation of Juncus tenuis, focusing on the isolation of phenanthrenes, and the preparation of semisynthetic derivatives of the isolated compounds. From the methanolic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…These results match those previously reported by other researchers, which highlighted an anti-proliferative activity of phenanthrenes and 9,10-dihydrophenanthrenes on several cancer cell lines derived from different tumor types, such as leukemia, breast, colon, prostate, and lung cancer [10,55]. Notably, several papers reported that similar molecules, at comparable doses, are effective on cancer cells and well tolerated by normal cells, suggesting a possible selective toxicity [56][57][58][59].…”
Section: Anti-proliferative Effects On Gastric Cancer Cell Linessupporting
confidence: 91%
“…These results match those previously reported by other researchers, which highlighted an anti-proliferative activity of phenanthrenes and 9,10-dihydrophenanthrenes on several cancer cell lines derived from different tumor types, such as leukemia, breast, colon, prostate, and lung cancer [10,55]. Notably, several papers reported that similar molecules, at comparable doses, are effective on cancer cells and well tolerated by normal cells, suggesting a possible selective toxicity [56][57][58][59].…”
Section: Anti-proliferative Effects On Gastric Cancer Cell Linessupporting
confidence: 91%
“…Phenanthrenes that have been isolated so far can be classified into three major groups by differences in their substitutents, which include monophenanthrenes, diphenanthrenes, and triphenanthrenes [ 3 ]. As of today, various biological activities of phenanthrenes have been reported, such as antimicrobial [ 3 ], antioxidant [ 4 ], anticancer [ 5 ], antiproliferative [ 6 ], anti-inflammatory [ 7 ], and antiallergic [ 8 ], and spasmolytic effects [ 3 ]. Moreover, phenanthrenes have been suggested to be a non-polar standard marker for genus Dioscorea [ 4 ].…”
Section: Introductionmentioning
confidence: 99%